Basin Evolution Palispatic Model of Bonaparte Basin, Australia Northwest Shelf - Nomensen Ricardo; Hendra Amijaya; Salahuddin Husein (Geological Engineering Department Universitas Gadjah Mada, 2018)
This research area is located on the Australian NW Shelf close to the westernedge of the Sahul Platform. This research is aimed to generate the palispatic basin model of Bonaparte Basin, Australian Northwest Shelf. It is to predict the impact of Neogene collision on the petroleum system distribution on Australian Northwest Shelf. The main data used in this research are seismic data using qualitative method analysis. The well data is used to well-seismic tied. After data acquisition, the seismic data are interpreted based on the horizon and structure interpretation. These interpretation are to reconstruct the basin evolution thorough geologic time. According to data analysis, the basin evolution palispatic model are divided into Paleo-proterozoic, Paleozoic, Triassic, Early Jurassic, Middle Jurassic, Late Jurassic, Early Cretaceous, Late Cretaceous, Early Eocene, Late Miocene and Recent condition. Regional tectonically there are at least three important events in NW Shelf: Middle Triassic-Jurassic NNE–SSW extension phase, Late Jurassic NE–SW extension phase and the Neogen collision phase; the Neogen collision effects on Northwest Shelf Australia. These three events contributed in forming and disturbing the Paleozoic and Mesozoic petroleum system in Bonaparte basin especially.